Land use impacts on climate - Güneralp, Burak; Zhan, Jinyan; Su, Hongbo; Deng, Xiangzheng (Springer Geography, 2014)
This book introduces a key issue in research on the climatic impact of land cover and land use changes via terrestrial biogeophysical processes. The parameterization of surface processes and a systematic approach to modeling the climatic impacts of land use change are discussed respectively, and can be used to improve parameterization schemes for climate numerical models and to provide a systematic method, thus offering more scientific and enhanced support for research on the climatic effects of land use/cover change. Further, based on predictions and scenario analyses of land use changes in typical zones, the climatic impact of various types of changes in different areas can be simulated through climatic numerical modeling, the simulation results are suitable for use in climate mitigation, land use planning, urban development planning, etc. Thus, the book is intended for researchers and professionals working in the area of meteorology systems, climatic numerical modeling, climate change, and land use/cover change, as well as decision makers in meteorology and land use planning. Professor Xiangzheng Deng is a senior research fellow at the Institute of Geographical Sciences and Natural Resources Research, Chinese Academy of Sciences.